2014
DOI: 10.1136/bcr-2013-203520
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery dissection after blunt chest trauma

Abstract: Blunt thoracic trauma may result in cardiac injuries ranging from simple arrhythmias to fatal cardiac rupture. Coronary artery dissection culminating in acute myocardial infarction (AMI) is rare after blunt chest trauma. Here we report a case of a 37-year-old man who had an AMI secondary to coronary dissection resulting from blunt chest trauma after involvement in a physical fight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Many studies describe MI as a direct result of cardiac injury due to trauma, most often blunt trauma. This often involves traumatic dissection of coronary arteries [2][3][4]. However, MI in trauma is not always associated with direct damage to the coronary arteries or myocardium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies describe MI as a direct result of cardiac injury due to trauma, most often blunt trauma. This often involves traumatic dissection of coronary arteries [2][3][4]. However, MI in trauma is not always associated with direct damage to the coronary arteries or myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to an aging demographic, the United States trauma population is becoming older, with greater chronic comorbidity [1]. Much of the literature regarding myocardial infarction (MI) in trauma discusses the effect of direct cardiac damage from chest trauma, but trauma patients can suffer from demand-related ischemic heart disease as well [2][3][4]. Trauma, like surgery, can cause physiologic stress which could potentially lead to cardiac ischemia and MI.…”
Section: Introductionmentioning
confidence: 99%
“…Andrew R Elms et al reported involvement of Left Circumflex coronary artery by penetrating pellets from gunshot resulting in Myocardial Ischemia. 15 Cases of blunt chest trauma resulting in dissection of LAD have been reported more in literature managed either conservatively 16 or by angioplasty. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…However, the shear force that is applied to the coronary artery wall via rapid deceleration can cause intimal tearing, whereas the generation of thrombosis has typically been considered the pathogenesis of occlusion [6] [17]- [19]. Therefore, in cases where CAG indicates simple occlusion, it is very possible that undetected intimal tearing may have occurred [18] [19]. When such intimal tearing exists, balloon angioplasty alone may allow a thrombus to re-form at that site [16].…”
Section: Discussionmentioning
confidence: 99%